Some Questions Regarding the Grounds and Procedure for Declaring the Invalidity of a Collective Employment Agreement - Chochova, Maria (Yearbook of the Law Department, 2021)
The exhibition addresses some issues regarding the procedure for declaring a collective agreement invalid. A comparison has been made between the claims for invalidity and those that can be filed in cases of non-performance of a collective labour agreement. Relevant case-law is analyzed.